Bede and the End of Time. By Peter Darby - Ahern, Eoghan (The journal of theological studies, 2013)
Of all the early medieval authors known to us, particularly in Anglo-Saxon England, few have received the same level of attention and scrutiny as the Venerable Bede. Yet, with more than 40 extant works, there are many areas of Bedan studies which require further exploration. Studies of his life and thought have tended to focus predominantly on Bede the historian at the cost of a more rounded treatment which acknowledges the importance of Bede the theologian and exegete, although recent scholarship has begun to move towards rectifying this imbalance.